Hierarchical Categorization: study review and possibilities of intervention on individuals with and without delayed development - Rosa, Bruna Nery; Silveira, Carolina Coury; de Almeida, João Henrique (Perspectivas em Análise do Comportamento, 2021)
The Relational Frame Theory (RFT) explains language and cognition based on the Arbitrarily Applicable Relational Responding (RRAA). One of the behaviors that can be explained from this perspective is hierarchical categorization. This study aimed to analyze the literature productions on hierarchical relational frames, focusing on assessment, teaching, and interventions on hierarchical categorization. Based on PRISMA protocol, searches were performed from the CAPES Journal Portal and included bibliographical references. By searching the Researchgate, publications met the following inclusion criteria: empirical studies related to RFT and relational training in hierarchy frame focused on establishing categorization. A total of 15 publications were included in the review and were classified into two categories: (a) Hierarchical Categorization Training and; (b) Others. The review results demonstrated few studies in relational, hierarchical frames, including populations with ASD. However, it was possible to pay attention to the efficiency of teaching procedures and the importance of promoting research in the area, especially in the population with ASD, to improve teaching curricula.